Предмет: Алгебра,
автор: rinatkuznecov766
спростить вираз (1-y)×3x²y-(3xy-x)xy
(a²-b²) (2a+b)-ab(a-b)
-3b(1-b²)(5b+2)
Ответы
Автор ответа:
0
Объяснение:
1. (1-y)*3x²y-(3xy-x)xy=3x²y-3x²y²-3x²y²+x²y=4x²y-6x²y²
2. (a²-b²)(2a+b)-ab(a-b)=2a³+a²b-2ab²-b³-a²b+ab²=2a³-b³-ab²
3. -3b(1-b²)(5b+2)=(-3b+3b³)(5b+2)=-15b²-6b+15b⁴+6b³
Похожие вопросы
Предмет: Русский язык,
автор: ГеоргийЕфимов
Предмет: Русский язык,
автор: dianavelishaeva
Предмет: Русский язык,
автор: НикельНаташа
Предмет: Математика,
автор: allahaciyeva
Предмет: Математика,
автор: cocirmariadenis